Cells, forces, and the microenvironment - Cuerrier, Charles M.; Pelling, Andrew E. (Physicsnetbase., 2015)
This book provides a broad overview of how mechanical forces and properties govern diverse aspects of physiological and pathological processes. It also covers new emerging techniques developed to study complex biosystems such as microfluidics, traction force microscopy, and the development of novel biomaterials for tissue engineering. Importantly, chapters in this book are not limited to applications in animal cell biology, but also cover important dimensions in other kingdoms such as plants and bacteria.